Multicentric small cell neuroendocrine neoplasm of the renal pelvis and ureter with concomitant focal high-grade urothelial carcinoma of the ureter: A case report - John S Banerji; Anila Korula; Jayalakshmi B Panicker (Indian Journal of Urology, 2008)
Malignant small cell neuroendocrine tumors of the pelvi-calyceal system are rare, and even more uncommon is their occurrence with concomitant transitional cell carcinoma, in the same renal unit. We present such a case for its unique presentation.